Modeling and Querying Multi-dimensional Moving Objects - SHEN Xiang-hong; WU Bing-ya; FANG Cheng-long; XU Jian-qiu; LIU Meng-yi (Journal of Harbin University of Science and Technology)
Motivated by the problem that the existing spatio-temporal data models do not fully represent moving objects, we design a multi-dimensional data model supporting multiple attributes, static and dynamic attributes. We design operators to manulate attributes by defining both syntax and semantics. The model is combined with spatio-temporal data model to enhance the capability of moving objects databases. We futher develop an index structure as well as the query algorithm to efficiently answer range queries over mult-dimensional moving objects. Each query defines both spatio-temporal and attribute parameters. We present the implentnation of a prototype system for dealing with multi-dimensional moving objects and use real moving objects data sets and synthetic attributes to conduct the experimental evaluation. The results demonstrate that (i) the proposed model well supports querying multi-dimensional moving objects, and (ii) the performance of our solution achieves more than one order of magnitude over alternative methods under the setting of 1 million moving objects with 400 attribute values.